Integration of a Network-Based and an Economy-Wide Water Model to Support Decision Making on Water Resources Planning and Management in Northeastern Brazil - Alcoforado de Moraes, Márcia M. G.; Souza da Silva, Gerald N.; Cunha, Marcelo Pereira da; Dias, Nilena B. M.; Cardoso, Terezinha F.; Guilhoto, Joaquim J. M.; Candido, Laíse Alves; Santos, Reinan R. S. (Frontiers in Water, 2021)
Allocation of Water Resources at the basin level is a critical issue for economic growth as well as for environmental sustainability. This study integrates network-based optimization with an Input-Output model, made available through a Spatial Decision Support System (HEAL), to support design and evaluation of water allocation policies. The innovative platform was applied to a case study using four-interlinked hydrographic basins in Northeastern of Brazil. The integrated modeling was able to measure broader socioeconomic impacts of decisions on reservoir volumes and water allocations at basin level, through indicators in a sectoral and regional scale, including ones associated with Sustainable Development Goals, such as the Water Use Efficiency (WUE) indicator. Results of the trade-offs between two scenarios, representative of the limits of performance of regulatory water instruments, were generated using the integrated modelling. They were compared with the Reference scenario for the base year (2011) and show that the economic sector most negatively affected by the regulatory instrument use is the industrial sector. Furthermore, the sugar and ethanol industry, main water users in the industrial sector (93.1% of the sector's water use) and less efficient (WUE 1.47 US$/m3 vs 30.70 US$/m3 average of the sector) in the base year, maintain their percentage share of water use in the sector and even slightly expand it (93.2%), with slight efficiency gains (+2.3%). On the other hand, non-water-intensive industries, have their shares reduced (from 6.9 to 6.8%) and lose efficiency (-9.5%). Results of the same trade-offs by region showed that the largest proportional economic losses occur in the drier areas, damaging the economy, especially in the most industrialized municipalities with the highest GDPs. Integrated economic modeling can expand aspects involved in water security issues, assisting management by introducing socioeconomic impact measures, in a broader scale, associated with allocation decisions. Hydrological allocation criteria cannot distinguish between user efficiency and which economic sectors are using how much water. This results in economic and social losses. In water-scarce regions and with growing transfer needs, such as in the basins studied, adequate incentives, through management instruments designed based on economic theory, are essential to promote sustainable development.